(untitled) (Nonlinear Studies, 2019)
In this paper, we present an existence theorem of solution for a boundary value problem of a nonlinear integrodierential equation of fractional order with integral boundary conditions by using measure of non compactness combined with xed point theorem of Monch. An example is given to illustrate our results.